2019
DOI: 10.3390/cancers11081187
|View full text |Cite
|
Sign up to set email alerts
|

4-Methylumbelliferone Inhibits Cancer Stem Cell Activation and Overcomes Chemoresistance in Ovarian Cancer

Abstract: We have recently shown that the extracellular matrix molecule hyaluronan (HA) plays a role in the development of ovarian cancer chemoresistance. This present study determined if HA production is increased in chemotherapy-resistant ovarian cancers and if the HA inhibitor 4-methylubelliferone (4-MU) can overcome chemoresistance to the chemotherapeutic drug carboplatin (CBP) and inhibit spheroid formation and the expression of cancer stem cell (CSC) markers. We additionally assessed whether 4-MU could inhibit in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 57 publications
2
40
0
2
Order By: Relevance
“…In fact, it has been shown that in many types of solid tumors, increased synthesis of HA by cancer cells or by tumor stromal cells is correlated with tumor growth and metastasis [ 9 , 142 ]. Recent studies have confirmed that the over-expression of HAS2 promotes tumor progression in breast, ovarian, bladder, colorectal, pancreatic and lung carcinoma and resistance to chemotherapy [ 143 , 144 , 145 , 146 , 147 , 148 ]. On the other hand, it was proved that inhibiting HA synthesis inhibits also metastasis of carcinoma cells in some types of tumors [ 144 , 149 ].…”
Section: Medical Applications Of Ha and Its Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it has been shown that in many types of solid tumors, increased synthesis of HA by cancer cells or by tumor stromal cells is correlated with tumor growth and metastasis [ 9 , 142 ]. Recent studies have confirmed that the over-expression of HAS2 promotes tumor progression in breast, ovarian, bladder, colorectal, pancreatic and lung carcinoma and resistance to chemotherapy [ 143 , 144 , 145 , 146 , 147 , 148 ]. On the other hand, it was proved that inhibiting HA synthesis inhibits also metastasis of carcinoma cells in some types of tumors [ 144 , 149 ].…”
Section: Medical Applications Of Ha and Its Derivativesmentioning
confidence: 99%
“…Recent studies have confirmed that the over-expression of HAS2 promotes tumor progression in breast, ovarian, bladder, colorectal, pancreatic and lung carcinoma and resistance to chemotherapy [ 143 , 144 , 145 , 146 , 147 , 148 ]. On the other hand, it was proved that inhibiting HA synthesis inhibits also metastasis of carcinoma cells in some types of tumors [ 144 , 149 ]. However, other studies reported that HAS3 that was associated with tumor progression, downregulate in early tumor development.…”
Section: Medical Applications Of Ha and Its Derivativesmentioning
confidence: 99%
“…In addition to the previous results, new therapies targeting both the ECM [20,293] and the MMPs are now emerging [294]. Since one of the main problems is that tumor ECM prevents the correct diffusion of drugs, numerous studies focus on either degrading the matrix, using collagenases, hyaluronidases or hyperthermia [295][296][297][298][299][300], and on blocking ECM synthesis de novo [301][302][303][304][305], although the latter has not provided positive results in clinical trials [306,307]. MMPs, which promote angiogenesis, metastasis and the release of factors within the matrix, are also the target of new therapies like andecaliximab and several MMPs antibodies, specific or broad-spectrum MMP inhibitors, which have shown promising results in clinical trials [294] (Fig.…”
Section: Clinical Implications and Future Trendsmentioning
confidence: 99%
“…Chemosensitive (n = 5) and chemoresistant (n = 7) primary cells were obtained from ascites of high grade OC patients before and after chemotherapy treatment as previously described [103]. Chemoresistance was determined when patients relapse and no longer respond to chemotherapy.…”
Section: Primary and Established Ovarian Cancer Cell Linesmentioning
confidence: 99%